The determinants of internal fraud using the fraud hexagon framework: a study of the banking sector listed on the Indonesia Stock Exchange - Zikria, Annisa; Winarningsih, Srihadi; Fatmawati, Faoziah Ulfah (Universitas Padjadjaran, 2026)
This study examines the determinants of internal fraud in Indonesian listed banks by applying the Fraud Hexagon framework (pressure, opportunity, rationalization, capability, arrogance, and collusion) to the banking sector on the Indonesia Stock Exchange (IDX) over 2020–2024. Internal fraud is operationalised as the number of internal fraud cases disclosed in each bank’s annual report during the study period. The analysis uses a balanced panel of 23 banks across five years (total 115 observations) and estimates a panel least squares model with cross-section fixed effects to control for time-invariant heterogeneity across banks. Pressure is proxied by the non-performing loan ratio, opportunity by the proportion of independent commissioners, rationalization by directors’ remuneration relative to net income, capability by board turnover, arrogance by CEO image frequency, and collusion by political connections. The model is jointly significant (Prob(F) = 0.0000) with substantial explanatory power (adjusted R² = 0.7706). However, none of the Fraud Hexagon proxies shows a statistically significant partial effect on internal fraud (p > 0.05), indicating that the proposed direct relationships are not supported in the fixed-effects specification. The findings suggest that disclosure-based internal fraud outcomes may be shaped by bank-specific factors and reporting practices, underscoring the need for richer fraud measurement and governance indicators in future research and improved process-level anti-fraud monitoring in practice.